Transnational social policies : the new development challenges of globalization - Morales-Gómez, Daniel A. (IDRC ; Earthscan, 1999)
Transnational Social Policies specifically addresses the worldwide trend for national policies on human and social development to be increasingly influenced by agendas that are international, or "transnational," in nature. In doing so, the book examines the underlining international developmental, ethical, economic, and political issues shaping national policies in health, education, and employment in the developing world. This book's focus on the "transnational" character of the social policy debate makes it a truly unique and original contribution to the literature. It will appeal to the acad.